Human Values of Main Character in Chappie Movie Directed by Neill Blomkamp - Cicih Nuraeni (LPPM Universitas Bina Sarana Informatika, 2017)
This research is presenting about human values as an element of fiction that applied in a movie entitled Chappie. The analysis is focus on finding how human values of main character that appear in the movie and the human values influence to the characterization of main character in Chappie movie. The methods of this research are descriptive qualitative method and library research to get the data. The data of this analysis are taken from Chappie movie directed by Neill Blomkamp. Furthermore, the researcher takes some theories from several books that related with the title to analyze human value of the main character in Chappie movie. The researcher is also identifies data and information from the theories. Hereafter, the researcher analyse the data to finds the problem to discuss deeply. The researcher uses basic human values theory by Shalom H. Schwartz. The result of this analysis are human values appear of main character when Chappie has self-direction, tradition, stimulation, achievement, and universalism in his behaviour. Human values influence the characterization of main character when he takes attention, perception, interpretation in situations, and the planning of action in his life. Keywords: human value; main character; movie